Epidermal Growth Factor Receptor Mutated Lung Cancer Presenting as Synchronous with a Recurrent Nonhuman Papillomavirus-Related Head-and-Neck Squamous Cell Carcinoma - Daphne Fonseca; Sahithi Shilpa Arya; Vaishnavi Kunteepuram; K. V. V. N. Raju; Senthil Rajappa (Journal of Integrated Health Sciences)
A patient with nonhuman papillomavirus (HPV)-related head-and-neck cancers is at an increased risk of developing second primary malignancies. We present a case of non-HPV-related squamous cell carcinoma (SCC) of the left lower alveolus who presented with locoregional recurrence in the left upper lip 3 years after initial treatment with chemoradiotherapy along with a synchronous Epidermal growth factor receptor(EGFR)mutated lung adenocarcinoma. Comprehensive genomic profiling will guide diagnosis and therapy in these cases. Registry of synchronous tumors would help design protocols for better management.